2017
DOI: 10.1016/j.jvs.2017.07.066
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of laparoscopic ligation of inferior mesenteric artery for the treatment of type II endoleak after endovascular aortic aneurysm repair

Abstract: Laparoscopic ligation of the IMA for treatment of type II endoleak after EVAR is a feasible and safe technique in specialized centers with high technical success rate and good midterm outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…Outcomes of transarterial embolisation: There is a relatively wide spread of reported technical and clinical success rates for this technique (Table 3 ), which is reflected in several meta-analysis and systemic reviews published recently [ 36 , 37 , 39 ]. One of the largest single cohorts published in 2012 of 95 patients undergoing 140 embolisation procedures (predominantly transarterial but a few other techniques too), using a range of embolics (glue 61%, coils 29%, glue and coils 7% and Gelfoam 3%) showed 81.5% freedom from aneurysm sac expansion at one year but a significant decrease to 43.7% at five years, with an associated increase in the number of repeat embolisation procedures required [ 40 ].…”
Section: Management Of Secondary Endoleaks—evarmentioning
confidence: 99%
“…Outcomes of transarterial embolisation: There is a relatively wide spread of reported technical and clinical success rates for this technique (Table 3 ), which is reflected in several meta-analysis and systemic reviews published recently [ 36 , 37 , 39 ]. One of the largest single cohorts published in 2012 of 95 patients undergoing 140 embolisation procedures (predominantly transarterial but a few other techniques too), using a range of embolics (glue 61%, coils 29%, glue and coils 7% and Gelfoam 3%) showed 81.5% freedom from aneurysm sac expansion at one year but a significant decrease to 43.7% at five years, with an associated increase in the number of repeat embolisation procedures required [ 40 ].…”
Section: Management Of Secondary Endoleaks—evarmentioning
confidence: 99%
“…108 Open conversion for T2ELs may be reasonably safe under elective circumstances, especially with endograft-preserving techniques. 109 Nevertheless, it arguably remains more invasive than any endovascular approach and typically less desirable given the significant medical comorbidities of patients selected for EVAR. 110…”
Section: Non-embolization Techniquesmentioning
confidence: 99%
“…No systematic reviews have directly compared endovascular interventions with open/laparoscopic treatments, although several systematic reviews of surgical approaches have been reported [44,45]. In these reviews, high technical success rates of 90% and 30-day mortality rates of 1.5% or 0% were reported.…”
Section: Surgical Interventionmentioning
confidence: 99%